Costs, structure and equity of international regimes for climate change mitigation - Carlo Carraro (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper provides an analysis of the effectiveness of climate policies by focusing on the link between policy options on the one hand, and structure of the agreements and of the international regimes on the other hand. In particular, the paper analyses whether there are the conditions for an agreement on climate change to be signed by all or almost all world countries; and whether some countries can play a strategic role, with respect to the goal of achieving the largest possible agreement, by proposing strategies, measures, institutions that help to expand the number of countries which commit to control their emissions. In this way, the paper also analyses which strategies can be proposed to reduce the costs of mitigation policies, where the cost reduction is achieved by increasing the number of signatories and by dividing more equitably the burden of emission control.
Keywords: H0; H2; H3; 330; Agreements; climate; incentives; negotiations; leakage; linkage; policy; transfers; Klimaschutz; Internationale Umweltpolitik; Umweltabkommen; Umweltkosten; Welt